2016
DOI: 10.1080/03019233.2016.1262574
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of fluid flow and desulphurisation kinetics in an argon-stirred ladle furnace

Abstract: A full-scale, three-dimensional, transient CFD modelling approach capable of predicting the threephase fluid-flow characteristics and desulphurisation behaviour in an argon-stirred ladle was developed. The model can accurately predict the molten steel flow and slag eye behaviour. The predicted sulphur content in ladle as a function of time agrees well with the experimental data. The effects of the initial sulphur content, the gas flow rate and the slag layer thickness on the desulphurisation efficiency were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Singh et al 21 and Hirasawa et al 44 stated that the slag thickness has little or almost no influence on k, meaning that only fluid flow in the metal phase is considered to influence the metalside mass transfer. In contrast, Kim and Fruehan 4 and Cao et al 33 found that a high volume of slag promotes a stronger circulation inside the slag layer. With the numerical approach, it is possible to investigate this phenomenon in greater detail.…”
Section: Effect Of Slag Thicknessmentioning
confidence: 96%
See 2 more Smart Citations
“…Singh et al 21 and Hirasawa et al 44 stated that the slag thickness has little or almost no influence on k, meaning that only fluid flow in the metal phase is considered to influence the metalside mass transfer. In contrast, Kim and Fruehan 4 and Cao et al 33 found that a high volume of slag promotes a stronger circulation inside the slag layer. With the numerical approach, it is possible to investigate this phenomenon in greater detail.…”
Section: Effect Of Slag Thicknessmentioning
confidence: 96%
“…The mixing phenomenon is well-characterized by several experimental 24 and mathematical [25][26][27][28][29][30][31] studies with or without the inclusion of a slag phase. However, an appropriate choice of a liquid-liquid mass transfer model in a CFD study is difficult to ascertain, and so only a few studies 21,32,33 have been conducted on this topic. Singh et al 21 developed a three-phase CFD model to determine the metalslag interfacial area using the VOF approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3) Desulfurization is one of the most important operations during the secondary refining process of steel, in practice it is common to use synthetic slag based on CaO and stirring with argon gas in the ladle furnace to improve the reaction kinetics at the interface steel-slag. However, the desulfurization mechanism is complex and depends on several operational variables involved in the process, such as the chemical composition of the slag, [4][5][6] injected gas flow, 7,8) temperature, 9) thickness of the slag layer, 10) refractory lining 11) and the content of dissolved oxygen in the steel. 12) In recent years, Computational Fluid Dynamics (CFD) coupled with kinetic models has been an alternative tool to analyze the behavior of desulfurization in a faster, cheaper and less hazardous way.…”
Section: Introductionmentioning
confidence: 99%
“…When the lance is outside the center of the ladle, shorter mixing times are obtained. [1] The study of phenomena, such as the behavior of fluid flow, the mixing efficiency, the opening of the slag layer, [2] the metal-slag reactions, [3,4] desulfurization efficiency, [3,5] and the behavior of inclusions, [6][7][8] have been widely investigated by the use of numerical modeling [2,9,10] as well as mathematical and physical simulation [1,2,[11][12][13][14][15][16] and validated with plant trials. [4] Numerical simulations worked in the modified arrangement of porous plugs and lances placed in an eccentric position at the bottom of the LF.…”
Section: Introductionmentioning
confidence: 99%